Role of DESH, callosal angle and cingulate sulcus sign in prediction of gait responsiveness after shunting in iNPH patients - Skalický, Petr; Vlasák, Aleš; Mládek, Arnošt; Vrána, Jiří; Bajaček, Michal; Whitley, Helen; Beneš, Vladimír; Bradáč, Ondřej (Journal of clinical neuroscience, 2021)
Primary endpoint of this single-centre, prospective consecutive cohort study was to evaluate DESH score, CA, CSS and Evans index of suspected iNPH patients against the reference standard of lumbar infusion test (LIT) and external lumbar drainage (ELD) in prediction of gait response after VP shunt implantation in patients with idiopathic normal pressure hydrocephalus (iNPH). Patients were assigned to NPH and non-NPH groups based on LIT and ELD results. Age-matched controls were added for group comparison. 32 NPH, 46 non-NPH and 15 control subjects were enrolled in the study. There were significant differences in mean preoperative DESH scores of NPH, non-NPH and control groups (6.3 ± 2.3 ([±SD]) (range 2-10) vs 4.5 ± 2.4 (range 0-10) vs 1.0 ± 1.2 (range 0-4)). Differences in mean CA and Evans index were not significant between NPH and non-NPH groups. CSS showed 62.5% sensitivity, 60.87% specificity, 52.63% PPV and 70% NPV for differentiation of NPH and non-NPH groups. A CA of 68 degrees had 48.49% sensitivity, 76.09% specificity, 59.26% PPV 67.31% NPV and DESH score of 4 had 93.75% sensitivity, 41.30% specificity, 52.63% PPV and 90.48% NPV for differentiation between NPH and non-NPH groups. The groups of probable iNPH patients with gait impairment diagnosed by high DESH score or positive functional testing did not overlap and DESH score did not correlate with gait improvement after ELD. DESH score should not be used as a simple diagnostic or prognostic marker of iNPH and we could not confirm the benefit of measurement of callosal angle and cingulate sulcus sign.
Keywords: Aged; magnetická rezonanční tomografie; ventrikuloperitoneální zkrat; Neuroimaging; lidé středního věku; senioři; Magnetic Resonance Imaging; lidé; Middle Aged; Prospective Studies; prospektivní studie; normotenzní hydrocefalus; Gait Disorders, Neurologic; Female; neurozobrazování; Cohort Studies; kohortové studie; neurologické poruchy chůze; ženské pohlaví; Humans; Hydrocephalus, Normal Pressure; Ventriculoperitoneal Shunt